BIOLOGICAL EFFECTS OF MONOSODIUM GLUTAMATE ON THE ORGANS OF THE NERVOUS SYSTEM - Rybalka, Ya.V.; Yeroshenko, G.A.; Shevchenko, K.V.; Kononenko, S.V.; Tymoshenko, Yu.V.; Sharlai, N.M.; Pyvovar, N.M. (World of Medicine and Biology, 2025)
In the body, monosodium glutamate is a mediator of the peripheral and central nervous systems. In both parts, it is related to metabolic and excitatory functions. Monosodium glutamate is widely used in the food industry as a flavor enhancer. Although food safety regulators generally recognize its safety for health, a number of studies have questioned its long-term safety. Taking into account all of the above, it can be assumed that monosodium glutamate, added to the diet in excessive amounts or with prolonged consumption, can cause behavioral, biochemical and morphological changes in structures such as the brain, hippocampus and cerebellum of adult mammals and lead to dysfunction in the central nervous system.